IR-spectroscopis investigation of foam hermetic on the basis of macroisocyanate - Іванов, С.В.; Масленнікова, Л.Д.; Грушак, З.В. (Proceedings of National Aviation University (archive), 2005)
Resuts of foamhermetics with on the base of poliamide and polymer that contains methylol groups investigations have been presented. Oxides were used to increase (porsiv ) hardntss of foam hermetics. IR-spectroscopis investigations have been performed by the basic lines method.